Advancing Digital Advertising: A Technical Deep Dive into Real-Time Ad Injection and HLS Streaming - Indrajit Shanbhag (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Over-the-Top (OTT) platforms have become more abundant, and at the same time, with the support of adaptive streaming protocols such as HTTP Live Streaming (HLS), a very dynamic but complex environment has emerged for digital advertising. There is high demand for scalable, targeted ad monetization, which would also be non-disruptive. Current methodologies not only face resistance from ad blockers but also introduce latency-induced buffering as well as fragmentation between legacy broadcast and modern digital ecosystems. This paper presents an original unified framework for real-time ad injection within HLS environments. They are three-fold: improved Server-Side Ad Insertion (SSAI) architecture capable of facilitating dynamic ad decisioning and seamless ad stitching, a hybrid model intended to connect advanced cloud-native ad servers to legacy broadcast infrastructures via standards-based workflows; technical innovations, among which are Low-Latency HLS (LL-HLS) optimizations for reducing buffering as well as opening up the transparency of the ad-tracking systems. Proof-of-concept results show a drastic reduction in the ad-failure rate, plus improved targeting accuracy and consistency of playbacks from different devices. In the end, this work acts as an easy-to-use and scalable pathway for media houses and content providers to maximize their revenues by ensuring continuous, seamless viewing experiences that put real-time HLS ad insertion at the heart of next-generation digital advertising.